Randomized Phase II Trial Comparing Carboplatin Plus Weekly Paclitaxel and Docetaxel Alone in Elderly Patients With Advanced Non‐Small Cell Lung Cancer: North Japan Lung Cancer Group Trial 0801. (28th March 2014) - Maemondo, Makoto; Inoue, Akira; Sugawara, Shunichi; Harada, Toshiyuki; Minegishi, Yuji; Usui, Kazuhiro; Miwa, Koji; Morikawa, Naoto; Kambe, Mariko; Ube, Kenji; Watanabe, Kana; Ishimoto, Osamu; et al.
Abstract : Background: Standard first‐line chemotherapy for elderly non‐small cell lung cancer (NSCLC) patients has been monotherapy with vinorelbine or gemcitabine. Docetaxel has also been considered as an alternative option for the elderly population in Japan. We have previously demonstrated the high efficacy of carboplatin plus weekly paclitaxel for elderly NSCLC patients. Consequently, we conducted a randomized phase II study to select the proper regimen for a future phase III trial. Methods: Eligible patients were aged 70 years or older with newly diagnosed advanced NSCLC. Patients were randomly assigned either to a combination of carboplatin (area under the curve: 6 mg/mL per minute) with weekly paclitaxel (70 mg/m 2 ) (CP regimen) or to single‐agent docetaxel (60 mg/m 2 ). The primary endpoint of this study was objective response rate. Secondary endpoints were progression‐free survival, overall survival, and toxicity profile. Results: Among 83 eligible patients (41 to CP, 42 to docetaxel), the objective response rates were 54% (95% confidence interval: 39%–69%) and 24% (95% confidence interval: 11%–37%) and median progression‐free survival was 6.6 months and 3.5 months in the CP arm and the docetaxel arm, respectively. Severe neutropenia, febrile neutropenia, and nausea were significantly frequent in the docetaxel arm, whereas toxicities in the CP arm were generally moderate. One treatment‐related death was observed in the docetaxel arm. Conclusion: The CP regimen achieved higher activity with less toxicity than single‐agent docetaxel. Considering the results of this phase II trial and the IFCT‐0501 trial, we have selected the CP regimen for a future phase III trial in elderly patients with advanced NSCLC. Abstract : 摘要 背景 . 长春瑞滨或吉西他滨单药治疗一直是非小细胞肺癌（NSCLC）老年患者的标准一线化疗。在日本，多西他赛也被视为老年人群的替代选择。我们在既往研究中发现卡铂联合每周1次紫杉醇用于老年NSCLC患者具有很高的疗效。因此，我们开展了本次随机化II期研究，以期为未来的III期试验选择合适方案。 方法 . 入组标准为≥70岁且新确诊为晚期NSCLC。患者随机分配至卡铂（曲线下面积：每分钟6 mg/mL）联合每周1次紫杉醇（70 mg/m 2 ）（CP方案）或单制剂多西他赛（60 mg/m 2 ）治疗。研究的主要终点为客观缓解率（ORR）。次要终点为无疾病进展生存期、总生存期以及毒性反应谱。 结果 . 83例合格患者（CP组41例，多西他赛组42例）中，CP组和多西他赛组ORR分别为54%（95%可信区间：39% ∼ 69%）和24%（95%可信区间：11% ∼ 37%），中位无疾病进展生存期分别为6.6个月和3.5个月。多西他赛组重度中性粒细胞减少、中性粒细胞减少性发热以及恶心的发生率明显更高，而CP组毒性反应普遍为中度。多西他赛组出现1例治疗相关死亡（TRD）。 结论 . 与单制剂多西他赛相比，CP方案获得的疗效更高，毒性反应更低。考虑到本次II期试验以及IFCT‐0501试验结果，我们选择CP方案用于未来在晚期NSCLC老年患者中开展III期试验。 The Oncologist 2014;19:352‐353